(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Most of the Indian English novels are centred around the cultural divide between the Orient and the Occident. However many of the novels invariably project the economic disparity between the two worlds. The novels under study, The Romantics A Novel and Making the Minister Smile repeatedly project the penury of India as if to satiate the palate the west. But such descriptions make compulsory probe into the nature of modernity and development.